An efficient differential evolution-based method for optimization of steel frame structures using direct analysis. (May 2023) - Vu, Quoc-Anh; Cao, Truong-Son; Nguyen, Thi-Thanh-Thuy; Nguyen, Huu-Hue; Truong, Viet-Hung; Ha, Manh-Hung
Abstract: Sizing optimization of steel frames using direct analysis is a highly complex optimization problem with discrete design variables and highly nonlinear constraints of structural safety and serviceability conditions. To tackle this problem, this study develops an improved differential evolution (DE), namely 2EpDE, with a new mutation technique using two p-best individuals. The results of twenty benchmark functions and four real-world constrained optimization problems prove that 2EpDE effectively saves computational efforts and searches for better global optimal solutions. A framework for the optimization of steel frames is then proposed using a combination of 2EpDE, Multi-Comparison Technique (MCT), and Promising Individual Method (PIM). The strength and serviceability constraints of the optimization are evaluated by direct analysis that can accurately perform the nonlinear inelastic behaviors of the structure. Two examples including two-story and six-story space frames are optimized to evaluate the efficiency of the proposed method. Compared to Jaya and Particle Swarm Optimization (PSO), the proposed method can save more than 35% of computational efforts and yields better optimum results.